Effect Of Nanoparticle Agglomeration In Solar Cell Formation - Azimov J.T. (Genius Journals, 2024)
This work allows us to discuss situations as the shape and radius of the ion particles affect the magnitude of surface charges. Also, this work considers the effect of nanoparticle agglomeration on the mechanical properties and durability of solar cells. The technique of ultrasonic dispersion is studied as a means for improving the uniformity of the distribution of nanoparticles in the resulting layer.
Keywords: solar cell, perovskite, nanoparticle agglomeration, surface, ionic bond agglomeration, ultrasonic dispersion.